2016
DOI: 10.1038/jp.2016.105
|View full text |Cite
|
Sign up to set email alerts
|

Elevated fecal calprotectin levels during necrotizing enterocolitis are associated with activated neutrophils extruding neutrophil extracellular traps

Abstract: BACKGROUND Neonates with necrotizing enterocolitis (NEC) have higher calprotectin levels in stool than do healthy neonates. However, it is not known whether high stool calprotectin at the onset of bowel symptoms identifies neonates who truly have NEC vs. other bowel disorders. STUDY DESIGN Neonates were eligible for this study when an x-ray was ordered to “rule-out NEC”. Stool calprotectin was quantified at that time and in a follow-up stool. Each episode was later categorized as NEC or not NEC. The location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 43 publications
4
36
0
1
Order By: Relevance
“…[20][21][22] Increased NET formation and accumulation may occur before, or close to the disease onset without proper clearance mechanisms, as shown for traumatized or septic adults. 39,40 NET formation in the intestine with released DNA and neutrophil-derived calprotectin has been shown to be associated with NEC, 26 but it was not clear if circulating NETs may play a role. In the present study, elevated circulating cfDNA levels 1-6 d before NEC onset in preterm infants suggest that sub-clinical systemic inflammation at an early stage of NEC may stimulate neutrophils to release DNA and antimicrobial proteins in the circulation, which may add further inflammatory insults that could advance NEC progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22] Increased NET formation and accumulation may occur before, or close to the disease onset without proper clearance mechanisms, as shown for traumatized or septic adults. 39,40 NET formation in the intestine with released DNA and neutrophil-derived calprotectin has been shown to be associated with NEC, 26 but it was not clear if circulating NETs may play a role. In the present study, elevated circulating cfDNA levels 1-6 d before NEC onset in preterm infants suggest that sub-clinical systemic inflammation at an early stage of NEC may stimulate neutrophils to release DNA and antimicrobial proteins in the circulation, which may add further inflammatory insults that could advance NEC progression.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 S100A8, which was highly upregulated (48.2-fold) in LOS + NEC pigs in the current study, is a subunit of calprotectin that was shown to be the key protein in the extruded NET structures in the intestine of patients with NEC. 26 Further, BPI and lactoferrin are among potent antimicrobial proteins released from neutrophils that may help to eliminate trapped bacteria. 13 Of note, up-regulated fibrinogen chains and vWF were among the nine circulating proteins involved in platelet activation and blood coagulation that differed between control and LOS + NEC pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this month's issue of the Journal of Perinatology, MacQueen et al [11] do an excellent job of demonstrating why diagnostic assays for NEC will not work until we understand not all NEC is the same disease and use NEC subsets for categorization. Previous research has demonstrated that calprotectin, an antibacterial protein, that is released from activated macrophages and neutrophils is generally increased in the stool of neonates with NEC compared to those without disease [12][13][14]. However, nearly all of these prior studies were limited in that they compared infants with diseased bowel to healthy term newborns.…”
mentioning
confidence: 92%
“…MacQueen et al [14] have previously reported that infants with bloody stools who did not progress to NEC had relatively low calprotectin levels. Likewise, in a previous publication, Christensen et al [18] reported that nearly half of all infants presenting with bloody stools had eosinophilia.…”
mentioning
confidence: 99%